2015
DOI: 10.1007/s13237-015-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic riddle of Chenopodium album L. complex (Amaranthaceae)

Abstract: C.album L. complex is a heterogenous assemblage of many taxonomic entities of cosmopolitan distribution. This is because many weedy and semi-domesticated forms have arisen due to hybridization and polyploidy. These distinct forms have been perpetuated by their breeding system characterized by high level of selfing and also by the phenological differences. The interrelationships in this aggregate of various taxa are now beginning to be explored. This is mainly because of the economic importance of many semi-dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These data suggest that C. album may include different photosynthetic types within a species. However, it is well known that C. album is a heterogenous assemblage of many taxonomic entities with cosmopolitan distribution, probably because many weedy and semi-domesticated forms have arisen by hybridization and polyploidization (Bhargava et al 2006;Ohri 2015). It has been recently suggested that hybridization may also be involved in the occurrence of C 3 -C 4 intermediates (Kadereit et al 2017;Ueno et al 2006).…”
Section: Photosynthetic Types In C Albummentioning
confidence: 99%
“…These data suggest that C. album may include different photosynthetic types within a species. However, it is well known that C. album is a heterogenous assemblage of many taxonomic entities with cosmopolitan distribution, probably because many weedy and semi-domesticated forms have arisen by hybridization and polyploidization (Bhargava et al 2006;Ohri 2015). It has been recently suggested that hybridization may also be involved in the occurrence of C 3 -C 4 intermediates (Kadereit et al 2017;Ueno et al 2006).…”
Section: Photosynthetic Types In C Albummentioning
confidence: 99%